A METHOD OF RAPID CULTIVATION OF RADISH SEED PLANTS IN PLASTIC POTS OF SMALL-VOLUME - V. A. Stepanov; T. V. Zayachkovskaya (Овощи России, 2017)
The development of cheap and rapid breeding methods to breed  the lines used for  hybrid  F1  production  is a very actual task. The study was carried out with a use of radish varieties originated at VNIISSOK and breeding lines obtained by crossing components of different origin with male  sterility  in  winter  glass  greenhouse.  The  mother plants were grown  on the trays Plantec 64, while seedplants were grown in plastic pots of 1 liter capacity. The some morphobiological features such as the small habitus of see-plant; smaller number of secondary branching and absence of following branches; and consequently, the low yield of seeds were revealed in seed-plants of radish being grown in plastic pots. The period of ontogenesis in radish at first winter-spring rotation with this cultivation approach was reduced to 92 days. At the second summer-autumn rotation with additional lighting the duration of period of ontogenesis was essentially shorter than in the first rotation.  The utilization of  small-volume capacities in winter glass greenhouse to grow the radish seed-plants has permitted to produce two generations a year.